The Need Of Culture-Based Arabic Reading Materials By Using Multimedia In Higher Education - Nuruddin Ali Muhtarom; Emzir Emzir; Shafruddin Tajuddin (Arabic Education Program IAIN Pekalongan, 2017)
This study aimed to describe the need of culture-based Arabic reading materials by using multimedia. It used research and development approach proposed by Borg and Gall. This study was started by collecting some information through literaturereview, observation, documentation, and interview of 10 students of Arabic Language department students of UNJ. The result of this study showed that there are some aspects of Arabic reading materials for students in higher educationthat should be developed. First, the learning theme. Some of the learning themes that should be discussed are: 1) campus life, 2) academic activities, 3)students achievement, etc. Second, the aspect of multimedia. In this case, the learning material is needed to be designed by using multimedia completed with list of vocabulary, lesson summary, and some explanation in the form of audio and video. Third, the aspect of culture. The perspective of Indonesian culture is really necessary to be included in the Arabic reading materials for students. Keywords: learning material, Arabic language skills, culture, multimedia